Diabetes Sleep Treatment Trial: Premise, Design, and Methodology - Chasens, Eileen R. (Contemp Clin Trials, 2018)
The Diabetes Sleep Treatment Trial (DSTT) is a multi-site, double-blinded, randomized, sham-controlled trial. The study objective is to test whether treatment of obstructive sleep apnea (OSA) with continuous positive airway pressure (CPAP) treatment results in improved glycemic control and diabetes self-management behavior compared to participants on a sham-CPAP (sub-therapeutic) device in participants with type 2 diabetes mellitus (T2DM) and co-morbid OSA. The purpose of this paper is to describe the premise for the DSTT, the study design, and the methodology used in this on-going trial. The target enrollment is 210 randomly assigned participants recruited from two sites. The primary outcome for glucose control is HbA1C; additional outcomes for diabetes self-management include objectively measured steps walked and subjectively measured diabetes-related distress, diabetes empowerment, and diabetes knowledge. All participants receive individual diabetes education and counseling for 6 weeks over two individual sessions and three telephone calls. Participants are randomized to receive either sham or active CPAP for 12 weeks, after which, they “guess” their group assignment; this will assist in determining the success of blinding participants to treatment group assignment. Participants revealed to be on active CPAP will be encouraged to continue CPAP for an additional 12 weeks; participants who had been on sham devices will be encouraged to have a repeat CPAP titration study and to crossover to active CPAP treatment for 24 weeks. An intention-to-treat approach will be used for efficacy analyses. The trial is registered with Clinicaltrials.gov (NCT01901055).